The impact of some morphological and motor characteristics in short distance running - Ramabaja, Q.; Rashiti, N.; Shkodra, M.; Ramadani, L. (Journal of Education, Health and Sport, 2021)
The knowledge of morphological development and their impact on motor skills in short-distance athletes should be one of the main concerns of athletics coaches, because any scientific research in the field of physical culture and sports is about proving the development and evaluation of anthropological characteristics which are responsible for achieving success in athletics. The purpose of this paper is to confirm the impact of some anthropometric characteristics in the execution of running speeds on short distances, specifically in running at 100, 200 and 400 meters to students aged 18 ± 6 years of the Faculty of Physical Education and Sports in Prishtina. The sample of this research has included a total of 60 students aged 18 years of the Faculty of Physical Education and Sports in Prishtina. The measurements were executed during September in the hall of the Faculty, while the 100, 200, and 400 meter runs in the stadium "Fadil Vokrri" Prishtina. The only condition that was used during the determination of the sample was: that the students are involved in regular physical education classes (and on the day of the measurement be healthy, without the flu, cold or other symptoms). The variables which are applied in this research have been 8 anthropometric variables and 3 motor-specific variables. The results obtained after their processing indicate that the impact of anthropometric variables is higher in running at 100, 200 and 400 meters. Short distance running and long distance running reduces the impact of anthropometric parameters whereas the influence of metabolic factors of energy production is increased. These results were also confirmed using regression analysis, so that groups of predictors of anthropometric characteristics, specific motor skills that statistically significantly influenced each variable of individual criteria. The world records below the 10-second limit, in the 100 m, near the 9-meter limit, show not only the high level of sports, but also the strong impact on the growth, especially of strength indicators, speed-strength, explosive force, as main and applied motor skills in sports and athlete’s everyday life.